Psychology Aspects of Eating Behaviors is a Nutrition and Health Problem - Erhan, Ergeshov; Laura, Bissenbayeva; Diana, Kalieva; Lyazzat, Abdulina; Zhanat, Bissenbayeva (Journal of Nutritional Therapeutics, 2019)
In recent years, overweight and obesity have reached the status of a global pandemic and are particularly prevalent in the world. Overweight and obesity identified as risk factors for several health problems, including type 2 diabetes, hypertension, coronary heart disease and stroke. In recognition of the fact that reducing the burden of obesity and overweight has the potential to decrease mortality and disease worldwide, the World Health Organisation established that promoting healthy diets and physical activity is now a public health priority. This research paper aims to discuss the nutrition and health problem as well as eating behaviour from the psychological aspects. This issue is very significant nowadays and considers it to be a global problem. Here the authors made research and analyses the background of this problem.